The Level of Tokophobia among Married Women ‎Sample - Al-Shagran, Hanan (Jordan Journal of Educational Sciences, 2023)
This study aimed to identify the level of Tokophobia in a sample of married women in Irbid province. A convenient sample of 634 married women was used for the study. To achieve the objectives of the study, the researcher used a descriptive survey method and translated the 25-item tokophobia scale (Nunes et al., 2021).The results showed that the level of tokophobia in the study sample was low and came after "self-perception of tokophobia " in the first place and at an average level, while the lowest mathematical averages came after "physical reflections". The results, further, showed that there are statistically significant differences attributable to the effect of age in favor of those aged less than 25 years in all dimensions except for "social participation". The results also showed no differences due to the impact of both the duration of the marriage and the number of pregnancies and employment. In light of the results, the researcher recommended raising health awareness among expectant or expectant mothers and elucidating the potential complications that may arise during pregnancy and childbirth